(untitled) (Journal of Medicine, 2009)
The stroke patients comprise a large number of hospital admissions and stroke is one of leading cause of significant mortality and morbidity. This prospective observational study was carried out among 100 hospitalized stroke patients admitted into different medicine units of Chittagong Medical College Hospital (CMCH), with a view to study clinical presentation and epidemiology of stroke. Data, collected in prescribed protocol, were analyzed in simple statistical percentage and cases were selected irrespective of age and sex. Stroke was found most commonly in 51-60 age group (45%in hemorrhagic and 51.75% in ischemic stroke).Most of the patients were male with male, female ratio 3:1 in hemorrhagic stroke and 1.35:1 in ischemic stroke. Most of the patients were from rural area (60% in hemorrhagic stroke and 57.5 in ischemic stroke). Ischemic stroke was found in 80% cases and hemorrhagic stroke was found in 20% cases. The commonest presentation in both ischemic and hemorrhagic stroke was hemiplegia or hemiparesis. Rightsided hemiparesis was the predominant finding in both types. Headache (60%) and vomiting (75%) were found to be more common accompaniment of hemorrhagic stroke. In case of ischemic stroke the association with these clinical features was less marked where headache was present in 46.25% and vomiting in 40% cases. 50% of patients of hemorrhagic stroke presented with Glasgow Coma Scale (GCS) level 9-12(grade2) and 5% with GCS level 4 - 8(Grade 3). Whereas, 52.5% of patients of ischemic stroke presents with GCS 9-12 and also 46.25% with GCS13-14 (grade 1). Hypertension was the commonest risk factor associated with both types of stroke. In hemorrhagic stroke it was 80% and in ischemic stroke it was found in 56.25% eases. Smoking was associated with 50% of hemorrhagic and 55% of ischemic stroke. Diabetes mellitus was associated with 26.25% of ischemic stroke doi: 10.3329/jom.v10i2.2820 J MEDICINE 2009; 10 : 86-89